TAS2R38 genotype predicts surgical outcome in nonpolypoid chronic rhinosinusitis. Issue 1 (12th November 2015) - Adappa, Nithin D.; Farquhar, Douglas; Palmer, James N.; Kennedy, David W.; Doghramji, Laurel; Morris, Shane A.; Owens, David; Mansfield, Corrine; Lysenko, Anna; Lee, Robert J.; Cowart, Beverly J.; Reed, Danielle R.; et al.
Abstract : Background: Over 550, 000 sinus surgeries are performed annually in the United States on patients with chronic rhinosinusitis (CRS). Although the results of sinus surgery vary widely, no known genetic factor has been identified to predict surgical outcomes. The bitter taste receptor T2R38 has recently been demonstrated to regulate upper airway innate defense and may affect patient responses to therapy. Our goal was to determine whether TAS2R38 genetics predicts outcomes in CRS patients following sinus surgery. Methods: A prospective study of patients undergoing sinus surgery evaluating postoperative outcomes through the 22‐item Sino‐Nasal Outcome Test (SNOT‐22). Patients were genotyped for TAS2R38 . Results: A total of 123 patients with CRS were initially analyzed; 82 patients showed nasal polyps (CRSwNP) and 41 patients were without nasal polyps (CRSsNP). Six months after surgery, the overall SNOT‐22 improvement was 25 ± 23 points. The TAS2R38 genotype was found to significantly correlate with surgical outcomes in patients without polyps; homozygotes for the functional receptor had a mean improvement of 38 ± 21, whereas heterozygotes or homozygotes for the nonfunctional receptor had a mean improvement of 12 ± 22 ( p = 0.006). This result was confirmed with a multivariate regression that incorporated further patients with 1‐month and 3‐month scores (n = 207). Conclusion: In patients undergoing sinus surgery for CRS, we have identified a genetic polymorphism that predicts variability in quality of life improvement following surgery at 6 months in nonpolypoid CRS. This is the first genetic polymorphism identified that has demonstrated to predict surgical outcome for a select group of CRS patients.